(untitled) (Rome, 2005)
The Workshop focused on emergency planning and responses to serious outbreaks of aquatic animal diseases in Asia. These proceedings include all the papers presented, group reports and resulting recommendations. The workshop was organized jointly by FAO, the Network of Aquaculture Centres in Asia-Pacific and the WorldFish Center and was hosted by the Government of Indonesia, Ministry of Marine Affairs and Fisheries. The material covers a wide range of topics, from a review of the history, current status and socio-economic impacts of transboundary aquatic animal diseases in Asia to analyses of regional needs in areas such as contingency planning, legislation and capacity building.
Keywords: Fish-culture